Optimasi Biaya dan Waktu dalam Penyusunan Jadwal Pelaksanaan Proyek (Studi Kasus Proyek Pembangunan Gedung Pusat Kegiatan Mahasiswa Universitas Diponegoro Semarang) - Amat Pawiro, Dadiyono; Suharyanto, Suharyanto; Atmojo, Pranoto Samto (Department of Civil Engineering, Diponegoro University, 2014)
Execution of conctruction project executed to pass selected project management system from planning phase until operation phase. Unfavorable scheduling system can cause the project to be inefficient. Execution of a construction project often needs to accelerate the duration of the project. Every effort to expedite the implementation of the project in general will result in increased project costs. This provides the necessary conditions so that the business dilemma that the project can be completed with optimum cost and time. The intention and purpose of this research is to accelerate the execution time by using the method of CPM overtime, so we get the optimal time and cost. This research method by forming a linear equation of the trajectory of the crisis and then analyzed by linier program LINDO. The results on the building construction projects the PKM Universitas Diponegoro obtained optimum time of 133 days with a total cost of Rp. 6,252,074,822,-